SRSF2 Mutations in Uveal Melanoma: A Preference for In-Frame Deletions? - van Poppelen, Natasha M. (Cancers (Basel), 2019)
Background: Uveal melanoma (UM) is the most common primary ocular malignancy in adults in the Western world. UM with a mutation in SF3B1, a spliceosome gene, is characterized by three or more structural changes of chromosome 1, 6, 8, 9, or 11. Also UM without a mutation in SF3B1 harbors similar chromosomal aberrations. Since, in addition to SF3B1, mutations in U2AF1 and SRSF2 have also been observed in hematological malignancies, UM without a SF3B1 mutation—but with the characteristic chromosomal pattern—might harbor mutations in one of these genes. Methods: 42 UMs were selected based on their chromosomal profile and wildtype SF3B1 status. Sanger sequencing covering the U2AF1 (exon 2 and 7) hotspots and SRSF2 (exon 1 and 2) was performed on DNA extracted from tumor tissue. Data of three UM with an SRSF2 mutation was extracted from the The Cancer Genome Atlas (TCGA). Results: Heterozygous in-frame SRSF2 deletions affecting amino acids 92–100 were detected in two UMs (5%) of 42 selected tumors and in three TGCA UM specimens. Both the UM with an SRSF2 mutation from our cohort and the UM samples from the TCGA showed more than four structural chromosomal aberrations including (partial) gain of chromosome 6 and 8, although in two TCGA UMs monosomy 3 was observed. Conclusions: Whereas in myelodysplastic syndrome predominantly missense SRSF2 mutations are described, the observed SRSF2 mutations in UM are all in-frame deletions of 8–9 amino acids. This suggests that the R625 missense SF3B1 mutations and SRSF2 mutations in UM are different compared to the spliceosome gene mutations in hematological cancers, and probably target a different, as yet unknown, set of genes involved in uveal melanoma etiology.